The Role Of Media And Retailer Message Recall On Malaysian Male Perceptions Of E-cigarette Use: The 2016 National Study Of E-cigarettes Prevalence - Lei Hum Wee; Guat Hiong Tee; Caryn Mei Hsien Chan; Samsul Draman; Ab Rahman Jamalludin; Bee Kiau Ho; Jane Miaw Yn Ling; Kuang Hock Lim; Muhammad Fadhli Mohd Yusoff; Nizam Baharom; Noorzurani Robson; Mira Kartiwi; et al. (Sage, 2024)
Indexed by WOS/SCOPUS/ERA